2020
DOI: 10.1111/gcb.15319
|View full text |Cite
|
Sign up to set email alerts
|

The soil microbial carbon pump: From conceptual insights to empirical assessments

Abstract: As a result of fossil fuel combustion, increasing greenhouse gas concentrations in the atmosphere are leading to global warming (Camill, 2010), which will continue to alter ecosystem services and degrade human welfare and well-being (Rossati, 2017). Global soil carbon (C) stocks are about three times greater than atmospheric C stocks (Jackson et al., 2017), so slight changes in soil organic C (SOC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(79 citation statements)
references
References 74 publications
6
73
0
Order By: Relevance
“…While our knowledge about soil C sequestration has been significantly advanced by the recent conceptual and technological breakthroughs (Cotrufo et al, 2019; Lehmann et al, 2020), how soils can be managed to efficiently sequester C remains a huge research gap. Emerging evidence reveals that SOC storage depends on the retention of C derived from both plants and microorganisms (Schmidt et al, 2011; Sokol et al, 2019; Zhu et al, 2020). Partitioning SOC into plant‐ and microbial‐derived C aids both in our understanding of the C formation pathways, as well as the mechanisms of SOC stability/persistence (Joergensen, 2018; Liang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While our knowledge about soil C sequestration has been significantly advanced by the recent conceptual and technological breakthroughs (Cotrufo et al, 2019; Lehmann et al, 2020), how soils can be managed to efficiently sequester C remains a huge research gap. Emerging evidence reveals that SOC storage depends on the retention of C derived from both plants and microorganisms (Schmidt et al, 2011; Sokol et al, 2019; Zhu et al, 2020). Partitioning SOC into plant‐ and microbial‐derived C aids both in our understanding of the C formation pathways, as well as the mechanisms of SOC stability/persistence (Joergensen, 2018; Liang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This process results in a thick layer of underground microbial residue, and their relatively stable storage contributes to the persistence of organic carbon in the soil 6,9 . Consequently, dynamic changes of these residues can significantly affect the balance of the terrestrial carbon budget 6,[9][10][11] . Dead remains of microorganisms (residual substance) can be traced by amino sugars; this can help in characterizing the source of SOC and estimating its stability potential [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, dynamic changes of these residues can significantly affect the balance of the terrestrial carbon budget 6,[9][10][11] . Dead remains of microorganisms (residual substance) can be traced by amino sugars; this can help in characterizing the source of SOC and estimating its stability potential [11][12][13] . Studies using advanced research methods have revealed that microbial carbon is important for the formation of stable soil SOC 10,[14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Among various natural and anthropogenic factors, the type (mineral and organic) and amount of fertilization play leading roles in maintaining or altering soil quality. For example, during the conversion from natural broad-leaf forest to tea ( Camellia sinensis L.) plantations, mineral fertilization decreased organic carbon (SOC) stock and hence negatively affected the soil quality (Fan and Han, 2018; Zhu et al, 2020). Long-term N fertilization commonly induces soil acidification (Guo et al, 2010; Kuzyakov et al, 2021, Geoderma).…”
Section: Introductionmentioning
confidence: 99%